2013
DOI: 10.1177/1059840513506942
|View full text |Cite
|
Sign up to set email alerts
|

Determination of School-Related Problems in Children Treated for Cancer

Abstract: This descriptive and case-control study was carried out in a pediatric oncology outpatient clinic to determine the school-related physical, social, and psychological problems and problems experienced in academic achievement of children treated for cancer. The sample of the study consisted of 56 Turkish patients with cancer, aged 7-18 years, who were in remission and attending school as well as their parents, a control group of patients who did not have cancer, and their teachers. A Child Information Form, a Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 23 publications
1
36
0
2
Order By: Relevance
“…Children from Spanish‐speaking families attended less school during treatment and were more likely to experience a delay in education. Previous studies have examined the impact of school attendance for pediatric cancer survivors, noting higher rates of absenteeism and grade repetition, but none have studied the experiences of Latino children. It is possible that less school attendance may reflect the already high rates of chronic school absenteeism reported for Latinos children of low‐income families in public schools .…”
Section: Discussionmentioning
confidence: 99%
“…Children from Spanish‐speaking families attended less school during treatment and were more likely to experience a delay in education. Previous studies have examined the impact of school attendance for pediatric cancer survivors, noting higher rates of absenteeism and grade repetition, but none have studied the experiences of Latino children. It is possible that less school attendance may reflect the already high rates of chronic school absenteeism reported for Latinos children of low‐income families in public schools .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, according to a recent meta-analysis 17 , children with ALL treated with chemotherapy alone scored lower on several neurocognitive domains including general intelligence, the Purdue Pegboard, and some aspects of executive function. Additionally, among childhood cancer survivors, there are deficits among many academic domains including mathematic performance and reading achievement as well as science, foreign languages, art, and music 23 . Furthermore, our results support the work of Reeves et al, which indicated reading ability among ALL survivors was predicted by sluggish cognitive tempo 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the necessity of CNS-directed treatment for event free survival, approximately 40% of pediatric ALL survivors experience neurotoxicity most commonly manifested as diminished cognitive abilities 715 . These same survivors are more likely than healthy peers or siblings to experience academic underachievement and repeat a grade 1623 . Although there is evidence that children with ALL are at risk for school-related problems, little is known about the potential impact of diminished cognitive abilities on academic outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations